2016
DOI: 10.1097/scs.0000000000002623
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of Parents of Children With Craniosynostosis by Objective Scoring of Patient Information Websites

Abstract: High-quality patient information on craniosynostosis does exist on the world wide web but may be difficult to find due to the complexity of factors used to rank websites on internet search engines. This results in some high-quality websites not appearing at the top of an internet search. Therefore, parents risk missing useful information relevant to their child's diagnosis. Healthcare professionals can use objective scoring of patient information websites to empower their patients to seek higher quality inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…This process has recently been investigated as a method to rank and navigate biomedical literature [70]. There is some evidence that higher ranked sites describing medical information have higher quality content and easier readability [71,72]; however, others do not corroborate these findings [73,74]. To our knowledge, few analyses of website content include search engine ranking, but this area should be investigated further as patients often equate popular sites with reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…This process has recently been investigated as a method to rank and navigate biomedical literature [70]. There is some evidence that higher ranked sites describing medical information have higher quality content and easier readability [71,72]; however, others do not corroborate these findings [73,74]. To our knowledge, few analyses of website content include search engine ranking, but this area should be investigated further as patients often equate popular sites with reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have highlighted the long-term emotional impact on the parents if the child's diagnosis and prognosis are not accurately and sensitively described (eg, Lalor et al, 2008; Costa et al, 2019). Previous research has shown that information about craniosynostosis is available online but can be difficult to access (Lloyd et al, 2016), yet, that even a brief information leaflet can reduce parental anxiety (Pidgeon et al, 2017). This study adds to the existing body of literature demonstrating the importance of providing accurate, individualized information at the point of diagnosis and throughout the treatment pathway, to reduce familial distress and facilitate the adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with publications on other conditions. [13][14][15][16] We also found that the term ''haemangioma'' is commonly misused to describe any type of vascular anomaly. This is also consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…This is also supported by previous research. [13][14][15][16] The reason for this could be multifactorial. Google uses over 200 factors in their ranking algorithm which include: keywords, site structure and security and speed, inbuilt links as well as users stored characteristics.…”
Section: Discussionmentioning
confidence: 99%